Evaluasi Strategi GMF Power Services - Hichmaed Tachta Hinggo S; Bambang Riyanto (Fakultas Ekonomi dan Bisnis Universitas Muhammadiyah Riau, 2018)
Abstract Business is something that can grow quickly, and therefore companies are required to have a strategy and can cause them. Business education strategies they run to do the same. In addition, the evaluation strategy also aims to see what is happening in strategy and strategy implementation at the time. This research uses qualitative approach and is a descriptive research type. This study aims to study and analyze strategies that implement GMF Power Services as a business unit of GMF. There are factors that can influence the strategy that has been implemented by GMF Power Services both internal and external factors. The results of this study found that one of the GMF Power Services strategy that can be used today is not in accordance with the current industry development.